2017
DOI: 10.1503/cjs.006116
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of revisional and primary bariatric surgery

Abstract: A comparison of revisional and primary bariatric surgeryBackground: Revisional surgery is an important component of addressing weight regain and complications following primary bariatric surgery. Owing to provincial need and the complexity of this patient population, a specialized multidisciplinary revision clinic was developed. We sought to characterize patients who undergo revision surgery and compare their outcomes with primary bariatric surgery clinic data. Methods:We completed a retrospective chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 24 publications
(21 reference statements)
2
18
0
3
Order By: Relevance
“…The rate of complications seen in this study is significant but it is comparable to those of other studies of revisional bariatric surgery [14][15][16]. Therefore, as with other revisional surgery, it is recommended that they are performed at large volume bariatric centres to minimise the risk.…”
Section: Discussionsupporting
confidence: 77%
“…The rate of complications seen in this study is significant but it is comparable to those of other studies of revisional bariatric surgery [14][15][16]. Therefore, as with other revisional surgery, it is recommended that they are performed at large volume bariatric centres to minimise the risk.…”
Section: Discussionsupporting
confidence: 77%
“…More distal alimentary anastomosis done in the ileum during SADI-S compared to biliopancreatic diversion was actually causing higher weight loss due to a potent ileal brake mediated by an enhanced secretion of the Table 6 Comparative analysis of blood markers levels before and after revisional surgeries hormones peptide YY and glucagon-like peptide-1 which are associated with increased satiety and decreased food intake [7]. We could duplicate results of the previous studies in terms of weight loss and TWL% with a slight advantage of SADI-S over OAGB-MGB [7,[16][17][18][19][20][21][22]. Multiple studies reported EWL% as 70-80% with superiority for SADI procedure when compared to RYGB post-LSG [16,20,21].…”
Section: Discussionmentioning
confidence: 90%
“…Unfortunately, co-morbidities often return with weight regain [ 5 , 6 ]. Surgical revisions may be attempted and have occasionally demonstrated improvements in obesity co-morbidities and weight loss, however, the risk of complications with revision procedures is significantly higher than with initial bariatric surgery [ 7 , 8 ]. While alternative surgical solutions for weight regain or inadequate weight loss exist, they do not prove to be sufficient long-term solutions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%